2022
DOI: 10.46827/ejes.v9i11.4521
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of School Climate on the Relationship Between Teacher Communication Behavior and Student Engagement

Abstract: The purpose of this study was to determine the mediating effect of school climate on the relationship between teacher communication behavior and student engagement. Utilizing quantitative, non-experimental design via correlational technique, data were obtained from 300 respondents of the study who are students who belong to the senior high school department, particularly Grade levels 11 and 12 of the three national high schools under the division of Davao Del Sur in the province of Davao Del Sur. The researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Furthermore, the study identified specific areas that could enhance a more conducive learning environment, such as promoting a positive and inclusive school culture and improving teacherstudent relationships. In Davao, Apostol and Delos Santos (2023) aimed to determine the mediating effect of school climate on the relationship between academic self-concept and student engagement in public secondary schools that offer the Senior High School Program. The research findings indicated that the mean scores for academic self-concept, student engagement, and school climate were all quite high.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the study identified specific areas that could enhance a more conducive learning environment, such as promoting a positive and inclusive school culture and improving teacherstudent relationships. In Davao, Apostol and Delos Santos (2023) aimed to determine the mediating effect of school climate on the relationship between academic self-concept and student engagement in public secondary schools that offer the Senior High School Program. The research findings indicated that the mean scores for academic self-concept, student engagement, and school climate were all quite high.…”
Section: Introductionmentioning
confidence: 99%